“Consider Yourself One of Us”: The Dickens Musical on Stage and Screen - Barker, Anthony (Text Matters: A Journal of Literature, Theory and Culture, 2017)
Charles Dickens’s work has been taken and adapted for many different ends. Quite a lot of attention has been given to film and television versions of the novels, many of which are very distinguished. The stage and screen musical based on his work, essentially a product of the last fifty years, has been neither as studied nor as respected. This paper looks at the connection between Dickens’s novels, the celebration of “London-ness” and its articulation in popular forms of working-class music and song. It will argue that potentially unpromising texts were taken and used to articulate pride and a sense of community for groups representing the disadvantaged of the East End and, more specifically, for first-generation Jewish settlers in London. This is all the more surprising as it was in the first instance through depictions of Oliver Twist and the problematic figure of Fagin that an Anglo-Jewish sensibility was able to express itself. Other texts by Dickens, notably Pickwick Papers, A Christmas Carol and The Old Curiosity Shop, were also adapted to musical forms with varying results, but the period of their heyday was relatively short, as their use of traditional and communitarian forms gave place in the people’s affection to manufactured pop/rock and operetta forms. I will argue that this decline was partly the product of changing London demographics and shifts in theatre economics and partly of the appropriation of Dickens by the academy.